Ontological difference, anthropological difference, and equal liberty. (11th February 2020) - Balibar, Étienne
Abstract: In this lecture, the author seeks to articulate in a systematic manner, although still tentative, the three ideas about which he has been developing his personal philosophy in the last period: "Ontological difference", which after Heidegger and Derrida needs to become redefined in terms of a quasi‐transcendental problematic of alterity; "anthropological difference", which covers the wholerange of oppositions which at the same time are inseparable from a representation of the "human" and impossible to define as invariable binaries; "equal liberty", the combination of heterogeneous values which, since Ancient democracies and Modern republican insurrections, has installed the tension of emancipation at the heart of the political institution.